2020
DOI: 10.1093/jn/nxaa162
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Mediate the Crosstalk Between Intestinal Epithelial Caco-2 Cells and Lactobacillus Plantarum WCFS1in an In Vitro Model with Intestinal Peristaltic Shear Force

Abstract: Background The intestinal epithelial cells, food molecules, and gut microbiota are continuously exposed to intestinal peristaltic shear force. Shear force may impact the crosstalk of human milk oligosaccharides (hMOs) with commensal bacteria and intestinal epithelial cells. Objectives We investigated how hMOs combined with intestinal peristaltic shear force impact intestinal epithelial cells and crosstalk with a commensal bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Another parameter to consider is the influence of the mechanical forces applied to the gut-on-chip system as compared with the Caco2 cells under static culture. A recent study highlighted that applying shear force equivalent to that experienced during intestinal peristalsis to Caco2 cells increased the modulating effects of HMOs on the gene expression of tight junction proteins [65], further supporting the importance of mechanical forces, such as flow and stretch to emulate the dynamic cellular microenvironment.…”
Section: Discussionmentioning
confidence: 92%
“…Another parameter to consider is the influence of the mechanical forces applied to the gut-on-chip system as compared with the Caco2 cells under static culture. A recent study highlighted that applying shear force equivalent to that experienced during intestinal peristalsis to Caco2 cells increased the modulating effects of HMOs on the gene expression of tight junction proteins [65], further supporting the importance of mechanical forces, such as flow and stretch to emulate the dynamic cellular microenvironment.…”
Section: Discussionmentioning
confidence: 92%
“…For example, gut-chip analysis of dimethyloxaloylglycine, a small molecule drug candidate for the prevention of radiation-induced gut permeability, predicted clinical outcomes in humans, while these results were not reproduced by rodent models 23 . Furthermore, evaluation of milk oligosaccharides and fermentate from SHIME microbial cultures displayed protein- and metabolite-dependent activation of claudin tight-junctional proteins, limiting small molecule transport as seen in longitudinal human studies involving B. infantis treatment of IBD 34 , 35 . To the best of our knowledge, gut-chip models have not previously been used to validate the in vivo function of synthetic biotics, making this study a foundational case study for evaluating dynamic processes such as strain activity, biomarker production, and host tissue responses, as well as for extrapolation of in vitro data to provide in vivo predictions.…”
Section: Discussionmentioning
confidence: 99%
“…No other study has examined the interactions between 3-FL and hBDs in an oral mucosa model, preventing us from comparing our results with the literature. Kong et al evaluated the effects of shear forces on the intestinal epithelial barrier with Caco-2 cells and, in addition, stimulated Caco-2 cells with 2 -FL, 3-FL, and lacto-N-triose II (LNT2) [13]. They found that shear force exposure downregulated antimicrobial peptide beta defensin (BD)-1 but that, under static and shear force conditions, LNT2-not 2 -FL or 3-FL-upregulated BD-1 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al evaluated the effects of shear forces on the intestinal epithelial barrier with Caco-2 cells and, in addition, stimulated Caco-2 cells with 2 -FL, 3-FL, and lacto-N-triose II (LNT2) [13]. They found that shear force exposure downregulated antimicrobial peptide beta defensin (BD)-1 but that, under static and shear force conditions, LNT2-not 2 -FL or 3-FL-upregulated BD-1 [13]. However, with Lactiplantibacillus plantarum WCFS1, all three HMOs upregulated BD-1 under shear force conditions, and 2 -FL and LNT2 did so under static conditions [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation